Comparative Analysis of Kidney Histomorphometry Utilizing Two Distinct Image Processing Software - Brahmadhi, Ageng; Ningrom, Ira Citra (Journal of biomedicine and translational research (Semarang), 2023)
ABSTRACTBackground: Histopathological examination is critical to evaluate tissue condition. An accurate assessment is necessary for diagnosis establishment. Nowadays, both quantitative and qualitative scoring are enhanced with computer-assisted image analysis to reduce bias. Various software was developed to assist in image analysis. The question of whether the measurement results from one software will be comparable to those from another software may come up, given the wide variety of software options. Nevertheless, this subject is only occasionally discussed.Objective: This study aimed to compare the measurement results from Fiji and QuPath software in kidney histomorphometry.Methods: Normal kidney histological slide was observed. Selected histological structures, including the renal corpuscle area, glomerular area, Bowman space area, inner diameter of proximal, distal, and Henle loop, were measured using QuPath and Fiji software. The measurement results from the two software were compared for value differences and agreement analysis.Results: The renal corpuscle means the area was 12.7x103 µm2 in QuPath and 12.5 x103 µm2 in Fiji. The glomerular area was 7.8 x103 µm2 for both software. The proximal tubule's inner diameters varied from 18.7 to 150.8 µm. Smaller inner diameters were observed in distal tubules (17.1-80.5 µm) and The Henle loop (15.5-69.6 µm). There was no significant difference in measurement results of particular structures between the compared software (P-value > 0.05). The further confirmational analysis supported the similarity between the two measurement results.Conclusion: the measurement result of kidney microstructures using QuPath and Fiji were identical.